2014
DOI: 10.1007/s10560-014-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Experience of Parents of Pre-pubescent Children with Gender Identity Issues

Abstract: Whilst in recent times there has been an increasing interest in the popular media in families with gender variant children, there is still a paucity of academic research into the experience of parenting a pre-pubescent child with gender identity issues. Gender dysphoria in young children engenders emotive reactions in adults meaning that social workers need to be aware of the various discourses surrounding gender identity in order to work sensitively with families affected. This research explores highly sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
(11 reference statements)
1
24
0
1
Order By: Relevance
“…While the surveys did not identify any significant changes in terms of self-efficacy, two of the interview participants illustrated how the program impacted on their sense of confidence, validating their parenting choices. Supporting these findings, education has been associated with a reduction in parents' anxiety (Hegedus, 2009) and confusion (Gregor et al, 2015), adding to a sense of their own empowerment (Cantner, 2012). Menvielle and Hill (2010) have highlighted similar benefits from a parent support group in the USA:…”
Section: Impact Of Education Program On Family Member Participantsmentioning
confidence: 95%
“…While the surveys did not identify any significant changes in terms of self-efficacy, two of the interview participants illustrated how the program impacted on their sense of confidence, validating their parenting choices. Supporting these findings, education has been associated with a reduction in parents' anxiety (Hegedus, 2009) and confusion (Gregor et al, 2015), adding to a sense of their own empowerment (Cantner, 2012). Menvielle and Hill (2010) have highlighted similar benefits from a parent support group in the USA:…”
Section: Impact Of Education Program On Family Member Participantsmentioning
confidence: 95%
“…Many research studies have shown that youth and adults experiencing gender diversity can face discrimination from professionals and have difficulties accessing healthcare (Dowshen et al, 2018;Gridley et al, 2016;Heard et al, 2018;Hyde et al, 2014;Snelgrove, 2012). Furthermore, caregivers and gender diverse individuals may feel healthcare professionals lack sufficient knowledge to provide well-informed care and are often left feeling maltreated and stigmatised as a result (Gregor et al, 2015;Gridley et al, 2016;McBride, 2018;Riggs, Coleman, & Due, 2014;Riggs & Due, 2015;Riley, Clemson, Sitharthan, & Diamond, 2013;Sharon, 2016). Several researchers have already clearly emphasised the need for a systemic understanding and whole-offamily support (Dierckx & Platero, 2018;von Doussa et al, 2017;Vanderburgh, 2008;Wolf-Gould, 2019).…”
Section: Access To Care For Gender Diverse Youthmentioning
confidence: 99%
“…This is additionally influenced by ethnic, cultural, and religious considerations, which are unique to each family. Whilst some family members may experience gender diversity positively, including forging closer family ties, others may experience a sense of loss and grief for the child, brother, or sister that once was (Field & Mattson, 2016;Gonzalez, Rostosky, Odom, & Riggle, 2013;Gregor, Hingley-Jones, & Davidson, 2015). The responses of siblings under the age of 18 years may be affected by their stage of development, understanding, and dependence on caregivers.…”
mentioning
confidence: 99%
“…Recent research by Gregor () also found that some parents of pre‐pubescent children struggle with psychoanalytic explanations and reject its credibility, preferring alternative conceptualizations propounded by psychologists such as Ehrensaft (2007, 2011a,b) that challenge gender identity disorder as a concept and reframe it. Gender‐variant behaviour is not seen as pathological but as part of an individual's creative expression of their identity.…”
Section: The Aetiology Of Gender Identity Issuesmentioning
confidence: 99%
“…, ) suggests that both parents and transgendered adults feel professionals are poorly educated about gender identity issues, especially in respect of younger pre‐pubescent children. Parental narratives frequently highlight their perception that many of the professionals they encountered along their journey were ill‐informed about gender dysphoria and thus were ill‐equipped to practice effectively with their family (Gregor ). This literature review thus endeavours to provide social workers with an overview of current research and theoretical paradigms, with a view to promoting understanding and better practice with families in this little understood field.…”
Section: Introductionmentioning
confidence: 99%